Association of MMP-2 (-1306 C>T), MMP-9 (-1562 C>T) Gene Polymorphism and the Formation of the Hematological Malignancies - Kaan SAVASOGLU; Mehmet EMIN ERDAL (Tehran University of Medical Sciences, 2016)
No Abstract